Effects of Boron Content on microstructure and mechanical properties of AlFeCoNiBx High Entropy Alloy Prepared by vacuum arc melting. (June 2019) - Hou, Lili; Hui, Jiatao; Yao, Yuhong; Chen, Jian; Liu, Jiangnan
Abstract: The AlFeCoNiB x ( x = 0, 0.05, 0.10, 0.15, 0.2) high entropy alloys are prepared by vacuum arc melting. The effect of B on the microstructure and mechanical behaviors of the alloys are systematically investigated. X-Ray Diffraction results and Electro-Probe Microanalyzer results show that small amount of B atoms are dissolved into B2 matrix and the other B atoms result in the formation of FCC phase. The addition of B content leads to transformation of microstructure from pure B2 phase to "B2 phase + particle FCC structure" and then to "B2 phase + eutectic structure". Eutectic structure consists of FCC1 phase and FCC2 phase. FCC1 phase is rich in Co and Ni and FCC2 phase is rich in B, Fe and Co. With the increase of B content, grain size of B2 phase firstly reduce and then increase. By increasing the B content from 0 to 0.2, fracture strength and plastic strain increase from 850 MPa to 2293 MPa and 0.07 to 0.27 respectively. The increase of yield strength is due to the solid solution strengthening and fine grain strengthening of boron atom. While, the increase of plasticity is due to the formation of FCC eutectic structure. Highlights: The results show that small amount of B are dissolved into matrix and the other B atoms result in the formation of FCC phase. when the B content is 0.15, grain size of B2 phase and eutectic structure is smallest, which means that a suitable amount of B can not only refine eutectic structure but also refine grain size. By increasing the B content from 0 to 0.2, the yield strength, fracture strength and plastic strain increase from 805 MPa to 1253 MPa, 850 MPa to2293 MPa and 0.07 to 0.27 respectively.